As dimensões econômica e social da sustentabilidade do turismo no município de Machadinho - RS - Lacerda, Luana Teixeira de (My University, 2019)
Tourism is an activity capable of generating income and social benefits for municipalities (RODERMEL, 2014) contributing to sustainable development from planned and constantly monitored actions (UNWTO, 2018; DIAS, 2005; BUTLER 1999; UNWTO, 2003). Considering this scenario, this paper aims to identify how the economic and social sustainability of tourism is presented in the municipality of Machadinho-RS, through the application of an adaptation of the Sustainability Indicators System for Tourist Activity – SISDTur (HANAI, 2009). To this end, we have used a research with a methodology of exploratory and descriptive nature, regarding the approach classified as quantitative, in the modality of case study, making use of a survey through the application of questionnaires for data collection. Among the dimensions of tourism sustainability, we have examined the social and economic sustainability of the tourism of Machadinho. The results indicated the sustainable potential of the existing activities, evidencing the benefits, mainly economical, as well as the future possibilities for the development of local tourism. It was found that both dimensions (social and economic) show, mostly, positive indicators, mainly the economic dimension which presented 30% of sustainable indicators and 55% potentially sustainable indicators. However, partially unsustainable results indicators have been found which demand attention as in the case of indicators which deal with projects of engagement of the residents in tourism, with programs aimed at social improvements of the local population, to the tourist communication, and to the value invested by the government in the sector. The information obtained from the local tourism agents provided the understanding of the touristic activity, based on the principles of sustainability, conceiving knowledge that help the development of the city and that guide other destinations regarding the structuring of tourism in their territories.
O Turismo é uma atividade capaz de gerar renda e benefícios sociais para os municípios (RODERMEL, 2014) contribuindo para o desenvolvimento sustentável a partir de ações planejadas e constantemente monitoradas (UNWTO, 2018; DIAS, 2005; BUTLER 1999; UNWTO, 2003). Considerando esse cenário este trabalho tem como objetivo analisar como se apresenta a sustentabilidade econômica e social do turismo no município de Machadinho – RS, por meio da aplicação de uma adaptação do Sistema de Indicadores de Sustentabilidade para Atividade Turística – SISDTur (HANAI, 2009). Para tanto, utilizou-se uma pesquisa com metodologia de natureza exploratória e descritiva, quanto à abordagem classificada como quantitativa, na modalidade de estudo de caso, fazendo uso de levantamento por meio da aplicação de questionários como técnica de coleta de dados. Dentre as dimensões da sustentabilidade turística, examinou-se a sustentabilidade social e econômica do turismo de Machadinho. Os resultados obtidos sinalizam para o potencial sustentável das atividades existentes, evidenciando os benefícios, principalmente econômicos, bem como as possibilidades futuras para o desenvolvimento do turismo local. Constatou-se que ambas as dimensões, social e econômica, apresentam, em sua maioria, indicadores positivos, com destaque para a dimensão econômica que apresentou 30% de seus indicadores sustentáveis e 55% potencialmente sustentáveis. Entretanto, foram encontrados indicadores que apresentam resultados parcialmente insustentáveis que demandam atenção, como é o caso dos indicadores que tratam sobre projetos de engajamento dos residentes no turismo, com programas voltados a melhorias sociais da população local, à comunicação turística e ao valor investido pelo poder público no setor. As informações obtidas com os agentes do turismo local proporcionaram a compreensão da atividade turística, tomando como base os princípios da sustentabilidade, concebendo conhecimentos que auxiliem o desenvolvimento do município de Machadinho e que orientem outros destinos quanto à estruturação do turismo em seus territórios.
Keywords: Turismo - Machadinho (RS); Sustentabilidade; Desenvolvimento sustentável; Tourism - Machadinho (Brazil); Sustainability; Sustainable development